Effect of ultraviolet radiation on the Nrf2 signaling pathway in skin cells - Ryšavá, Alena; Vostálová, Jitka; Rajnochová Svobodová, Alena (International journal of radiation biology, 2021)
PURPOSE: Excessive exposure of skin to solar radiation is associated with greatly increased production of reactive oxygen and nitrogen species (ROS, RNS) resulting in oxidative stress (OS), inflammation, immunosuppression, the production of matrix metalloproteinase, DNA damage and mutations. These events lead to increased incidence of various skin disorders including photoaing and both non-melanoma and melanoma skin cancers. The ultraviolet (UV) part of sunlight, in particular, is responsible for structural and cellular changes across the different layers of the skin. Among other effects, UV photons stimulate oxidative damage to biomolecules via the generation of unstable and highly reactive compounds. In response to oxidative damage, cytoprotective pathways are triggered. One of these is the pathway driven by the nuclear factor erythroid-2 related factor 2 (Nrf2). This transcription factor translocates to the nucleus and drives the expression of numerous genes, among them various detoxifying and antioxidant enzymes. Several studies concerning the effects of UV radiation on Nrf2 activation have been published, but different UV wavelengths, skin cells or tissues and incubation periods were used in the experiments that complicate the evaluation of UV radiation effects. CONCLUSIONS: This review summarizes the effects of UVB (280-315 nm) and UVA (315-400 nm) radiation on the Nrf2 signaling pathway in dermal fibroblasts and epidermal keratinocytes and melanocytes. The effects of natural compounds (pure compounds or mixtures) on Nrf2 activation and level as well as on Nrf2-driven genes in UV irradiated human skin fibroblasts, keratinocytes and melanocytes are briefly mentioned as well.HighlightsUVB radiation is a rather poor activator of the Nrf2-driven pathway in fibroblastsUVA radiation stimulates Nrf2 activation in dermal fibroblastsEffects of UVA on the Nrf2 pathway in keratinocytes and melanocytes remain unclearLong-term Nrf2 activation in keratinocytes disturbs their normal differentiationPharmacological activation of Nrf2 in the skin needs to be performed carefully.
Keywords: Ultraviolet Rays; NF-E2-Related Factor 2; ultrafialové záření; signální transdukce; Reactive Oxygen Species; keratinocyty; lidé; Skin; faktor 2 související s NF-E2; transkripční faktor GABP; kůže; Keratinocytes; reaktivní formy kyslíku; Humans; GA-Binding Protein Transcription Factor; Signal Transduction